THE INFLUENCE OF LIFESTYLE, SOCIAL CLASS AND BRAND IMAGE ON IPHONE PURCHASE DECISION AMONG YOUNG PEOPLE IN MANADO - Mamosey, Grasia Putri; Mangantar, Maryam; Saerang, Regina (Universitas Sam Ratulangi, 2025)
This study aims to analyze the influence of lifestyle, social class, and brand image on the purchasing decisions of young people in Manado, Indonesia, regarding iPhones. This research is quantitative in nature, with data collected through questionnaires distributed to 100 young respondents (aged 16-30) who use iPhones. The study utilizes multiple linear regression model with the assistance of SPSS 23. The sampling technique used is purposive sampling, which is a type of non-probability sampling. The results of the study show that: 1. Lifestyle, Social Class and Brand Image all simultaneously have an influence on the IPhone Purchase Decision among young people in Manado. 2. Lifestyle has an influence on iPhone Purchase Decision among young people in Manado. 3. Social Class does not have an influence on IPhone Purchase Decision among young people in Manado. 4. Brand Image has an influence on iPhone Purchase Decision among young people in Manado. Keywords: Purchase Decision, Lifestyle, Social Class, Brand Image